Preoperative warming combined with intraoperative skin-surface warming does not avoid hypothermia caused by spinal anesthesia in patients with midazolam premedication - Vanni, Simone Maria D’Angelo (2007)
CONTEXT AND OBJECTIVE: Inadvertent perioperative hypothermia is common during spinal anesthesia and after midazolam administration. The aim of this study was to evaluate the effects of intraoperative skin-surface warming with and without 45 minutes of preoperative warming in preventing intraoperative and postoperative hypothermia caused by spinal anesthesia in patients with midazolam premedication. DESIGN AND SETTING: Prospective and randomized study at Hospital das Clínicas, Universidade Estadual Paulista, Botucatu. METHODS: Thirty patients presenting American Society of Anesthesiologists (ASA) physical status I and II who were scheduled for elective lower abdominal surgery were utilized. The patients received midazolam premedication (7.5 mg by intramuscular injection) and standard spinal anesthesia. Ten patients (Gcontrol) received preoperative and intraoperative passive thermal insulation. Ten patients (Gpre+intra) underwent preoperative and intraoperative active warming. Ten patients (Gintra) were only warmed intraoperatively. RESULTS: After 45 min of preoperative warming, the patients in Gpre+intra had significantly higher core temperatures than did the patients in the unwarmed groups (Gcontrol and Gintra) before the anesthesia (p < 0.05) but not at the beginning of surgery (p > 0.05). The patients who were warmed intraoperatively had significantly higher core temperatures than did the patients in Gcontrol at the end of surgery (p < 0.05). All the patients were hypothermic at admission to the recovery room (TCORE < 36° C). CONCLUSIONS: Forty-five minutes of preoperative warming combined with intraoperative skinsurface warming does not avoid but minimizes hypothermia caused by spinal anesthesia in patients with midazolam premedication.